Bronchoscopic transparenchymal nodule access (BTPNA): first in human trial of a novel procedure for sampling solitary pulmonary nodules - Herth, Felix; Eberhardt, Ralf; Sterman, Daniel; Silvestri, Gerard A.; Hoffmann, Hans; Shah, Pallav L. (Thorax, 2015)
Introduction The promise of benefits from lung cancer screening is tempered by the false positive rate and the need to perform diagnostic procedures to determine the aetiology of the solitary pulmonary nodules (SPN) identified. We have developed a novel procedure which allows sampling of SPNs via a transparenchymal approach, and report the results from this as a first in human trial. - Methods This study was a prospective single-arm interventional study. We recruited patients with a SPN detected on CT imaging, which was suspicious for lung cancer, who were suitable for surgical resection. Using the subject's CT, an optimal airway wall point of entry (POE), and an avascular path through lung tissue from the POE to the SPN was calculated. A tunnel tract was created from the POE to the nodule using a set of catheter-based tools under fused fluoroscopy guidance. The patients proceeded to surgical resection immediately after the biopsy. The participants were followed-up for 6 months after the procedure. The primary endpoint of the study was to evaluate the feasibility to access and biopsy the nodule. - Results Twelve patients were recruited, and a tunnel pathway created in 10 patients. There were no adverse events during the procedures. Adequate biopsies were obtained from 10 patients (83%), which correlated with the histological findings from the surgical resection. Inspection of the resected lobes did not raise any safety concerns and indicated appropriately tunnelled pathways to the nodule. - Conclusions This first in human study demonstrates that bronchoscopic transparenchymal access of SPNs is feasible. - Trial registration number NCT02130115.
Gesehen am 31.08.2020